Articles Illustration of “Semangat Pelanusa” on Pelanusa Community Merchandise as a Promotional Media - Syahid, Muhamad Ihsan; Jeremiah, Sean Elbert (LPPM STIKI Malang, 2024)
Pelanusa is a community in Malang that focuses on crafts and community empowerment. However, from the many activities carried out by this community, there are still many people who do not know about the Pelanusa community and also ineffective promotional media. This research aims to design illustrations on Pelanusa community merchandise as a promotional medium to introduce the values and identity of the community to the wider community. The research methodology uses a qualitative approach with data collection through interviews and observations and the use of the Design Thinking method which consists of the Empathize, Define, Ideate, Prototype, and Test stages. The results showed that the merchandise successfully attracted the attention of the community, as evidenced by the positive response during the community exhibition at Kebun Winih, Singosari. Visitors were interested in buying merchandise because of its creative design and relevance to the identity of Pelanusa Community. In addition to being a product, this merchandise serves as an effective visual promotional medium, because its use by the community indirectly introduces the community to a wider audience. This research concludes that designing merchandise illustrations can be an effective promotional strategy, while strengthening the image and values of the community.